Peran Kebijakan Pesantren dalam Menanamkan Sikap Tasamuh Santri di Era Digital pada Pondok Pesantren Darul Falah Padang Lawas - Dwi Asri; Wisnu Fadillah; Rahmad Riski Hutagalung; Tiara Indah Lestari Pane; Tengku Darmansah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of Darul Falah Islamic Boarding School's policy in instilling an attitude of tasamuh (tolerance) among students amidst the challenges of the digital era is the subject of this research. In addition to offering many conveniences, the digital era has also become a tool for spreading exclusive ideologies, hoaxes, and hatred that threaten tolerance. As an Islamic educational institution, Islamic boarding schools have a responsibility to protect their students. This research collected data through in-depth interviews with Islamic boarding school leaders, ustadz, and students, as well as observation activities and analysis of policy documents (qanun). A qualitative approach, case study method, was used. The results of the study show that Darul Falah Islamic Boarding School implements three levels of policy: (1) Curricular Policy that focuses on the study of moderate yellow books (fiqh muqaranah and tasawuf) as the theological basis of tasamuh; (2) Student Policy that encourages discussion and interaction (such as bahtsul masail) with strict sanctions for bullying; and (3) Digital Adaptive Policy that establishes strict regulations on the use of gadgets and the